Enhanced saccharification of wheat straw with the application of ultrasonic-assisted quaternary ammonium hydroxide pretreatment. (February 2017) - Zhong, Chao; Jia, Honghua; Wei, Ping
Graphical abstract: Highlights: Combined mechanical-chemical pretreatment for wheat straw was designed. Pretreated straws with great lignin removal and structure disruption were obtained. Process analysis of pretreatment was conducted to determined significant factors. 4-fold enhanced saccharification yield (∼92%) was achieved from pretreated straws. Lignin could be partially recovered and collected from straw via pretreatment. Abstract: Lignocelluloses featuring complicated structure and poor degradability usually require pretreatment before its utilization. In this study, an ultrasonic-assisted pretreatment by using quaternary ammonium hydroxide was introduced to enhance biodegradability of lignocellulosic biomass. The synergistic chemical and mechanical pretreatment were supposed to be responsible for both external surface destruction and internal structure disruption of lignocelluloses. High-efficient lignin removal accompanied with obvious structural (crystallinity) transformation was achieved in the pretreated straws. Process analysis indicated that factors of time, temperature, concentration of solvent, and ultrasound power intensity turned out to be significant for pretreatment, and a 4-fold increased saccharification yield of around 92.4% as compared to untreated straw was obtained from the wheat straw pretreated by 15% solvent at 50 °C for 0.5 h in power intensity 344 W/cm 2 . All results suggest that the combined chemical and mechanical treatment can significantly improve the bio-accessibility of lignocelluloses, leading to the enhanced utilization efficiency.